Mantuq dan Mafhum - Nabila, Sovie Najwa (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
Ushul Fiqh science is a science that discusses the elaboration of rules in determining Islamic sharia law derived from the arguments of the Qur'an. in the science of ushul fiqh there is a discussion of the istinbath method. ushul fiqh experts have made the istinbath method in several categories, including Mantuq and Mafhum. As for this research, it uses the method of Library Research or Literature Study which is done by searching for sources related to Mantuq and Mafhum. The results found are based on the research that has been done, the results obtained that what is meant by Mantuq is expressed by pronunciation according to speech (explicit meaning), which is based on the material of the letters called mantuq understanding. while Mafhum is the meaning of a lafadz that can be understood. and both have several kinds and rules.